Dual enhancement of superconductivity in FeSe/SrTiO 3 via orbital and correlation synergy - Guihao Jia; Jingming Yan; Yucong Peng; Shendong Su; Pei Ouyang; Xiaopeng Hu; Qi-Kun Xue; Wei Li (Proceedings of the National Academy of Sciences, 2026)
In iron-based superconductors, the d z 2 orbital band typically resides far below the Fermi level and has not been considered to participate in Cooper pairing. Here, using monolayer FeSe/SrTiO 3 as a model system, we demonstrate that tip-induced tensile strain controllably shifts the d z 2 band toward the Fermi level, driving a two-stage enhancement of superconductivity. In-plane lattice expansion first enhances electronic correlation, amplifying superconductivity in the initial stage. As strain further increases, the upward-shifted d z 2 band hybridizes with the d xy band, reconstructing the pairing-active d -orbital bands and inducing a secondary, stronger gap enhancement. Collectively, these two stages enlarge the superconducting gap from 17.8 to 23.6 meV. Throughout this process, invariant Fermi wave vectors confirm that the enhancement originates from band renormalization and reconstruction rather than carrier doping. Our work establishes a route to tailor superconducting states via strain-activated electronic correlations and band engineering, and reveals a previously unrecognized orbital-selective pairing mechanism with broad implications for correlated multiband superconductors.